Experimental Observation of Non-'S-Wave' Superconducting Behavior in Bulk Superconducting Tunneling Junctions of Yba 2 Cu 3 O 7-δ - Guerra, Leandro Jose; Basco, Flordivino; Sarmago, Roland (Science Diliman: A Journal of Pure and Applied Sciences; Vol 10 No 1 (1998), 2007)
Evidence of non-s-wave superconductivity from normal tunneling experiments in bulk tunneling junctions of YBa 2 Cu 3 O 7-δ is presented. The I-V and dI/dV characteristics of bulk superconducting tunneling junctions of YBa 2 Cu 3 O 7-δ have been measured at 77.0K and clear deviation from s-wave superconducting behavior has been observed. The result agrees with d-wave symmetry, and interpreting the data in this way, the magnitude of the superconducting energy gap, 2Δ, is found to be (0.038 ± 0.002) eV. Comparing this energy gap with T c (2Δ/k B T c = 5.735), indicates that these high-T c superconductors are strongly correlated materials, which in contrast with BCS-superconductors are believed to be weakly correlated.